Quantifying cooperative flow of fat crystal dispersions. Issue 14 (22nd March 2022) - Milc, Klaudia W.; Dijksman, Joshua A.; van Duynhoven, John P. M.; Terenzi, Camilla
Abstract : Route to quantification of cooperative flow behaviour of fat crystal dispersions with tuneable microstructural properties. Abstract : We quantify the cooperative flow behaviour of fat crystal dispersions (FCDs) upon varying crystallization conditions. The latter enabled altering the multiscale microstructure of the FCDs, from the nanometer-sized platelets, and the dispersed fractal aggregates, up to the strength of the mesoscopic weak-link network. To the goal of characterizing strongly-confined flow in these optically-opaque materials, we acquire high-resolution rheo-magnetic-resonance-imaging (rheo-MRI) velocimetry measurements using an in-house developed 500 μm gap Couette cell (CC). We introduce a numerical fitting method based on the fluidity model, which yields the cooperativity length, ξ, in the narrow-gap CC. FCDs with aggregates sizes smaller than the confinement size by an order of magnitude were found to exhibit cooperativity effects. The respective ξ values diverged at the yield stress, in agreement with the Kinetic Elasto-Plastic (KEP) theory. In contrast, the FCD with aggregates sizes in the order of the gap size did not exhibit any cooperativity effect: we attribute this result to the correspondingly decreased mobility of the aggregates. We foresee that our optimized rheo-MRI measurement and fitting analysis approach will propel further similar studies of flow of other multi-scale and optically-opaque materials.